Riemann solution for a class of morphodynamic shallow water dam-break problems - Zhu, Fangfang; Dodd, Nicholas (Cambridge University Press, 2018)
This paper investigates a family of dam-break problems over an erodible bed. The hydrodynamics are described by the shallow water equations, and the bed change by a sediment conservation equation, coupled to the hydrodynamics by a sediment transport (bed load) law. When the initial states ~Ul and ~Ur are sufficiently close to each other the resulting solutions are consistent with the theory proposed by Lax (1973), that for a Riemann problem of n equations there are n waves associated with the n characteristic families. However, for wet-dry dam-break problems over a mobile bed, there are 3 governing equations, but only 2 waves. One wave vanishes because of the presence of the dry bed. When initial left and right bed levels (Bl and Br) are far apart, it is shown that a semi-characteristic shock may occur, which happens because, unlike in shallow water flow on a fixed bed, the flux function is non-convex. In these circumstances it is shown that it is necessary to reconsider the usual shock conditions. Instead, we propose an implied internal shock structure the concept of which originates from the fact that the stationary shock over fixed bed discontinuity can be regarded as a limiting case of flow over a sloping fixed bed. The Needham & Hey (1991) approximation for the ambiguous integral term RhdB in the shock condition is improved based on this internal shock structure, such that mathematically valid solutions that incorporate a morphodynamic semi-characteristic shock are arrived at.